PHOTOCATALYTIC DECOMPOSITION OF ACETAMIPRID (PESTICIDE) BY PPE-1/NiO NANOPARTICLES (Scientific journal of the Fergana State University, 2025)
The aim of this research work is to reduce environmental hazards associated with pesticides, and to this end, the photocatalytic degradation of the agricultural pesticide acetamiprid using a photocatalyst based on a functional polymer nanocomposite using PPE-1/NiO nanocomposite is described, and the results obtained by HPLC-MS analysis are analysed. According to it, it was observed that free radicals (superoxide anion (O2-), hydrogen peroxide (H2O2) and hydroxyl radical (OH-)) decompose acetamiprid into intermediates in the oxidation-reduction process and after a certain time into lower molecular weight (m/z 60, CH3COOH) during the photocatalysis process.